Peningkatan Produktivitas Benih Jagung (Zea Mays L.) Hibrida Varietas MZ dengan Pengaturan Split Planting: Penelitian - Jihan Luthfia, Jihan Luthfia; Suharno, Suharno; Budi Wijayanto, Budi Wijayanto (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Split planting is a technical cultivation management in the form of implementing a difference in planting time between male and female parents. The purpose of this study was to determine the effect of split planting on increasing productivity and flowering synchronization in the production of hybrid corn seeds of the MZ variety. This study was conducted using a split plot design method with a split plot design. The treatments used were 4 levels of split planting. The parameters observed consisted of flowering age, nicking observations, fresh and dry weight of cobs, number of kernels and weight per cob, and yield productivity. Data analysis using Analysis of Variance (ANOVA) at the 5% level of data with a significant effect will be further tested using the BNJ Test at the 5% level. The results showed that the split plating treatment 0-3-5 (0 HST female planting, 3 HST male 1 planting, and 5 HST male 2 planting showed the most optimal nicking synchronization, where male 1 tassel shading 5-7% when silk was in the range of 1-2%, and both reached 100% simultaneously on the 8th to 10th day. Male 2 functioned effectively as a reserve when it became active on the 3rd to 4th day. This study found the right split planting arrangement for the production of hybrid corn seeds of the MZ variety with an increase in productivity from 3.19 tons/ha with a 0-2-4 split planting arrangement to a significant increase of 7.11 tons/ha with a 0-3-5 split planting arrangement.